A Conceptual Framework on the Financial Statement Disclosure in Indonesia Local Government - Nurlianto, Oktavia; aswar, khoirul (Journal of Economics and Behavioral Studies, 2020)
This research begins with the problem of the Indonesian Minister of Finance recognizing cities and districts in Indonesia have a low level of compliance regarding financial reports and the Supreme Audit Board (BPK) has published a report that highlights compliance issues in the local government of Indonesia based on the Summary of First Semester Examination Results in 2019 there is a problem of the level of compliance of local government related to the disclosure of financial statements in Indonesia. The purpose of this study was to determine the factors influencing the degree of mandatory disclosure to local governments in Java and Sumatra Islands. This study has three objectives namely to find out the number of local parliamentarians, local government budget spending, existence of an assistance and training program for disclosure financial statement. Therefore, this research contributes to provide an illustration for local governments in measuring financial statement disclosures.